INDONESIA - JAPAN RELATIONS IN THE TECHNICAL INTERNSHIP PROGRAM (TIP) - Saragih, Hendra Maujana; Zulham, Muhammad; Mulyana, Mario Risdantino (Universitas Nasional, 2020)
Labor problems have become commonplace in Indonesia. This is due to the large number of productive people in Indonesia who have increased over time. Cooperation between Indonesia and Japan in human development to become a superior workforce with the Technical Internship Program is a solution for Indonesia in reducing the unemployment rate. Indonesia as a country that aims to reduce the unemployment rate is not only limited to taking advantage of the program. TIP is one of the factors that strengthen the relationship between Indonesia and Japan in the economic field. This paper uses the theory of cooperation, theory of interdependence and theory of bilateral relations as a case analysis knife that the author wants to discuss. The author uses qualitative research methods in dissecting the issues discussed.